Building Effective Communities of Practice: Best Practices from ASU ShapingEDU + the CoAction Learning Lab. v3.0 December 2019 - Becker, Samantha; Geringer, Laura; Dick, Angela; Flintoff, Kim; Kroll, Christine; Pickett, Alexandra; Signorelli, Paul; Stephens, Lisa; Sullivan, Rachel; Garcelon, Ray; Paulson, Elan; Wetzel, Ryan; et al. (2019)
Collaborators from higher education institutions across the globe share lessons learned from their experiences and exemplars leading and participating in communities of leadership/practice.